VARIASI SERAPAN KARBONDIOKSIDA (CO2) JENIS-JENIS POHON DI âECOPARKâ, CIBINONG DAN KAITANNYA DENGAN POTENSI MITIGASI GAS RUMAH KACA - Hidayati, Nuril; Mansur, M.; Juhaeti, Titi (Buletin Kebun Raya, 2013)
This research aims to assess the contribution of biological diversity in CO2 absorption by analyzing the physiological characteristics (CO2 absorption, transpiration, stomatal conductance, leaf chlorophyll content) of tree species in a conservation area of âEcoparkâ, Cibinong. The results were meant to provide information on CO2 absorption of some tree species suitable for revegetation. The results showed that there was a wide range of variation of CO2 assimilation rate among tree species. The overall CO2 assimilation rate ranged from 2.86 to 16.45Â  Âµmolm-2s-1. The highest CO2 absorption was Pometia pinnata (16.45Â  molm-2s-1), followed by Garcinia xanthochymus (11.40 Âµmolm-2s-1), Syzygium polyanthum (10.99 Âµmolm-2s-1), Syzygium polycepaliodes (10.89 Âµmolm-2s-1), and Palaquium obtusifolium (10.41 Âµmolm-2s-1). Transpiration rate was recorded between Â 1.29 mmolm-2s-1 (Maniltoa grandiflora)Â  and 7.85 mmolm-2s-1 (Euphoria longan). The rate of CO2 assimilation was affected by solar radiation and thus the quantum leaf (Q leaf), stomatal conductance, as well as leaf chlorophyll content. Trees species that have characteristics of high CO2 absortion and efficient in maintaining water balance (low transpiration rate), are suitable for green house gas mitigation.Â Â